(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study investigates the relationship between maternal mortality and economic growth in Nigeria. Design/Methodology/Approach: The study uses secondary data from the World Development Indicators and UNESCO Institute for Statistics. It employs a multiple regression analysis model to assess the impact of maternal mortality and other economic variables on Nigeria’s GDP. Findings: Results indicate that the maternal mortality ratio (MMR) and capital stock (K) negatively correlated with GDP. However, while capital stock (K) significantly affects GDP, MMR is insignificant. Additionally, variables such as education, exports, and arable land show a positive but statistically insignificant relationship with GDP at the 5% significance level. The R² value of 0.8613 suggests maternal mortality accounts for approximately 86% of Nigeria’s economic growth variance. Research Limitation: The study relies on secondary data sources, which may have inherent limitations in accuracy and completeness. Practical Implication: Reducing maternal mortality could have long-term economic benefits by improving workforce productivity and human capital development. Social Implication: Healthier mothers lead to healthier families and communities, ultimately reducing poverty and improving overall social well-being. Originality/Value: This study contributes to the discourse on population and economic growth by empirically examining the link between maternal mortality and economic performance in Nigeria. This area has received limited scholarly attention. The insights provided can inform policymakers on the economic importance of improving maternal health outcomes.